The Effect of Communication and Accuracy of Beauty Clinic Outpatient on Patient Satisfaction Moderated by Medical Records at Muntira Skin Care - Renni Yuniati; Adrie Frans Assa (Syntax Corporation Indonesia, 2026)
Patient satisfaction is a key indicator of healthcare service quality influenced by various factors, including therapeutic communication and service accuracy. This study analyzed the influence of therapeutic communication and the accuracy of beauty clinic outpatient services on patient satisfaction, with medical records as a moderating variable. Using a quantitative approach with a cross-sectional design, the study involved 160 patients from Muntira Skin Care as respondents. The results showed that therapeutic communication and beauty clinic outpatient service accuracy positively and significantly affected patient satisfaction. Furthermore, medical records were found to significantly moderate the relationship between both independent variables and patient satisfaction. These findings confirm that empathetic communication, service timeliness, and integrated medical records are key factors in improving patient satisfaction in beauty clinics. This research provides theoretical contributions by enriching healthcare management studies and developing patient satisfaction models with medical records as a moderating variable, as well as practical contributions as input for Muntira Skin Care in improving service quality through communication training, service flow optimization, and investment in electronic medical record systems. The managerial implications emphasize the importance of continuous communication training for staff, optimization of service flows to reduce waiting times, and investment in integrated electronic medical record systems to comprehensively improve patient satisfaction.